A hard pill to swallow. Issue 6 (26th June 2020) - Thompson, Angus
Abstract : Difficulty swallowing oral medication is a common problem, particularly among older patients, and all kinds of factors may cause issues: tablets may be too large, too small or the wrong shape. Here, Angus Thompson suggests some possible solutions, which are as diverse as the problems themselves.